2018
DOI: 10.1177/1042258718796080
|View full text |Cite
|
Sign up to set email alerts
|

When Do Women Make a Better Table? Examining the Influence of Women Directors on Family Firm’s Corporate Social Performance

Abstract: Our paper seeks to further understand the influence of gender board diversity on firms' corporate social performance (CPS) in the context of publicly-held family firms. Grounded on corporate governance and family firm literature, we argue that the influence of women directors on CSP will be contingent on their relative power and legitimacy within the board, and that such dynamics are particularly important in family firm boardrooms. Our empirical results show that increases in CSP associated to the presence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
108
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(117 citation statements)
references
References 74 publications
7
108
0
2
Order By: Relevance
“…As women directors have been viewed as paying more attention to the welfare of the natural environment and other external stakeholders (Krüger, ; Li et al, ; Lu & Herremans, ; Post et al, ; Walls et al, ), family owners would expect women directors to be sympathetic to family's interests in the case of an environmental CSR agenda and thus, if appointed, to use their influence on the board to bring this agenda about. Recently, Cruz, Justo, Larraza‐Kintana, and Garcés‐Galdeano () found that women nonfamily outsiders and women family insiders do enhance corporate social performance in family firms, due to their relative power and legitimacy vis‐à‐vis other directors. We interpret this finding as being consistent with the view that controlling family owners are likely to know that women directors will support their environmental CSR preferences and therefore seek to appoint them to advance their environmental CSR agenda.…”
Section: Theoretical Framework and Research Hypothesesmentioning
confidence: 99%
“…As women directors have been viewed as paying more attention to the welfare of the natural environment and other external stakeholders (Krüger, ; Li et al, ; Lu & Herremans, ; Post et al, ; Walls et al, ), family owners would expect women directors to be sympathetic to family's interests in the case of an environmental CSR agenda and thus, if appointed, to use their influence on the board to bring this agenda about. Recently, Cruz, Justo, Larraza‐Kintana, and Garcés‐Galdeano () found that women nonfamily outsiders and women family insiders do enhance corporate social performance in family firms, due to their relative power and legitimacy vis‐à‐vis other directors. We interpret this finding as being consistent with the view that controlling family owners are likely to know that women directors will support their environmental CSR preferences and therefore seek to appoint them to advance their environmental CSR agenda.…”
Section: Theoretical Framework and Research Hypothesesmentioning
confidence: 99%
“…Hearn (2011) shows that family firms in North Africa have larger boards mainly because of the presence of independent directors, which positively influence their post‐initial public offering (IPO) returns. Firms with institutional investors and family control in the United States are also associated with larger boards that devise more corporate social responsibility (CSR) engagement and diversification strategies (e.g., Cruz, Jusko, Larraza‐Kintana, & Garcés‐Galdeano, 2019; Lungeanu & Ward, 2012; Walls, Berrone, & Phan, 2012). In addition, state‐owned Chinese firms have larger boards that restrict loan collateral (An et al, 2016).…”
Section: Current State Of the Fieldmentioning
confidence: 99%
“…The article by Cruz et al (2019) raises some interesting questions. Conceptually, the article draws attention to role identities and gender stereotypes in family firms, a topic that has received increasing, but still insufficient attention (e.g., Amore, Garofalo, & Minichilli, 2014;Martinez-Jimenez, 2009; Rodrı´guez-Ariza, Cuadrado-Ballesteros, Martı´nez-Ferrero, & Garcı´a-Sa´nchez, 2017).…”
Section: Intra-firm Social Relationshipsmentioning
confidence: 99%